2019
DOI: 10.1111/jch.13752
|View full text |Cite
|
Sign up to set email alerts
|

High blood pressure in dementia: How low can we go?

Abstract: Hypertension is an important public health concern. The prevalence keeps increasing, and it is a risk factor for several adverse health outcomes including a decline in cognitive function. Recent data also show that the prevalence of hypertension and TAKEDA Pharmaceuticals International; and has received grants for clinical research from Microlife Co., Ltd. J Sison has received honoraria from Pfizer, AstraZeneca, AmGen, Boehringer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The HOPE Asia Network has published a number of papers on important Asia‐specific topics in hypertension . This Asia‐specific issue of the Journal of Clinical Hypertension provides an important resource including original research and review articles on the management of hypertension from a variety of Asian viewpoints, including topics such as central BP, environmental factors, comorbidities such as diabetes, atrial fibrillation, heart failure, and dementia, recent Asian guidelines and so forth . This issue also includes reports from twelve countries/regions in Asia to help define and highlight the current status of hypertension, its management, and their initiatives.…”
Section: Resultsmentioning
confidence: 99%
“…The “perfect 24‐hour BP control” strategy taking Asian characteristics into account is essential for achievement of the “zero” cardiovascular event goal . Considerable work has already been done on the journey to achieving this goal . Practically, a staged approach to the 24‐hour management of hypertension should be considered, first targeting morning hypertension, then nocturnal hypertension, followed by daytime hypertension .…”
Section: Perspectivesmentioning
confidence: 99%
“…Hypertension is considered a more important risk factor for mortality in dementia patients without AF compared to those with AF due to the different ways in which hypertension and AF impact cardiovascular health and contribute to death ( 31 , 32 ). Hypertension can increase the risk of mortality by damaging blood vessels and increasing the risk of cardiovascular events ( 33 ), such as AF, heart attack and stroke, which can lead to death. In addition, hypertension can also worsen the underlying dementia and contribute to functional decline and decreased quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…However, in later life, low blood pressure may induce cerebral hypoperfusion, and therefore, lead to a neurodegenerative process and accelerate the clinical manifestations of cognitive impairment [29]. In a recent review, the optimal target for lower systolic blood pressure value was found 120-130 mmHg, especially in nondiabetic hypertensive patients with significant risk factors for dementia [30].…”
Section: Discussionmentioning
confidence: 99%